Comparison of skin and shoe marker placement on metatarsophalangeal joint kinematics and kinetics during running. (January 2023) - Perrin, T.P; Morio, C.Y.M; Besson, T.; Kerhervé, H.A; Millet, G.Y; Rossi, J.
Abstract: This study investigated the effects of marker placement (skin- vs shoe-mounted) on metatarsophalangeal joint (MTP) kinematics and kinetics during running. Fifteen trained men ran on a 15-m track at 10 and 13 km/h with three (low, standard and high stiffness) shoe longitudinal bending stiffnesses (LBS). Reflective markers were fixed on the shoe upper, and on the skin using holes cut in the shoe. Three-dimensional marker positions and ground reaction forces were recorded at 200 and 2000 Hz, respectively. Kinematic and kinetic parameters were analyzed using one-dimensional metrics (statistical parametric mapping). MTP joint was less dorsiflexed at midstance ([57% to 100%] of braking phase and [0% to 48%] of pushing phase), and the MTP joint plantarflexion moment was higher ([22% to 55%] of pushing phase) with the shoe markerset in comparison with the skin markerset. The effect of LBS on MTP angle was found to be significant for a larger percentage of each stride using the shoe markerset compared to the skin markerset. However, the effect of LBS on plantarflexion moment was significant with the shoe markerset only. The effect of running speed on MTP angle was significant for a larger percentage of each stride with the skin markerset. This study demonstrates that the placement of markers influences the measurement of MTP kinematics and kinetics and that these effects are mediated by other variables such as LBS or running speed. It is concluded that the shoe markerset does not fully reflect the movement of the MTP joint.